2017
DOI: 10.1098/rsfs.2016.0075
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of aerial righting in wingless nymphal stick insects

Abstract: Numerous wingless arthropods as well as diverse vertebrates are capable of mid-air righting. We studied the biomechanics of the aerial righting reflex in first-instar nymphs of the stick insect Extatosoma tiaratum. After being released upside-down, insects reoriented dorsoventrally and stabilized body posture via active modulation of limb positions and associated aerodynamic torques. We identified specific reflexes for bilaterally asymmetric leg displacements which elicit body rotation and subsequently stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…This behaviour, which may serve as a defence reaction, is also likely to be valid for the wingless species C. morosus. Immediately after falling from a height, the stick insects are able to reorientate and stabilize their body during the plunge (Zeng et al, 2017), and land on their tarsi (M.S., T.H.B., S.N.G. and H.R., unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…This behaviour, which may serve as a defence reaction, is also likely to be valid for the wingless species C. morosus. Immediately after falling from a height, the stick insects are able to reorientate and stabilize their body during the plunge (Zeng et al, 2017), and land on their tarsi (M.S., T.H.B., S.N.G. and H.R., unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that several insects are capable of aerial righting in mid-air, e.g. wingless pea aphids 27 and wingless stick insect nymphs 28 . However, the time scale of the reported behaviours is significantly longer than that of the jumps reported herein and hence it is probable that aerial righting does not contribute significantly in the present case.…”
Section: Resultsmentioning
confidence: 99%
“…For example, ants (Yanoviak, Munk and Dudley, 2011), spiders (Yanoviak, Munk and Dudley, 2015) and stick insect instars (Zeng et al, 2017) have been shown to use coordinated motions of their legs and appendages during falling to initiate, reorient and stabilize their body orientation.…”
Section: Discussionmentioning
confidence: 99%